Pengaruh Knowledge Management Dan Teknologi Informasi Terhadap Keunggulan Bersaing Dan Kinerja Universitas - Siti Samsiah (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
This study aims to find whether there is influence of knowledge management and information technology on competitive advantage and performance of private universities in Pekanbaru. This research is a survey research with the technique of distributing questionnaires to teaching and employees. The sample used in this study amounted to 320 people consisting of 222 teaching and 98 employees. Hypotheses were tested using Partial Least Square with SmartPLS version 2.0 software. The results of testing of the proposed hypothesis show evidence that knowledge management has an influence on the competitive advantage and performance of private universities in Pekanbaru, but not with the information technology variables that show the results have no effect on the competitive advantage and performance of private universities in Pekanbaru.